UJI AKTIVITAS ANTIMALARIA IN VIVO DARI BEBERAPA FRAKSI EKSTRAK KULIT BUAH MANGGIS (Garcinia manggostana Linn) PADA MENCIT (Mus musculus ) YANG DIINFEKSI DENGAN Plasmodium berghei - Iqbal, Muhammad; Effendi, Zulham; Aamruna, Yaum; Suryawati, Suryawati (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Malaria disease is still one public health problem in the world and affect the infant mortality rate, under five and pregnant women. The purpose of this study was to recognize in vivo antimalarial activity from hexane fraction, ethyl acetate, and methanol extracts of mangosteen peel and the most active fraction as antimalarial. Laboratory experimental research with a post-test only with control group design and total random sampling design consists of 1 negative control group and 4 treatment groups. 75 Swiss strains which are male mice, healthy, 1.5-2.5 months of age and 20-30 gr body weight were selected randomly to exemineÂ 3 fraction was prepared with levelized fractionated and macerated method. Each treatment group received 0.2 ml dose of drug test suspension 10; 30; 90 and 270 mg/kgBW/day orally, whereas the control group was given arabic gum suspension 0.1% on day 2 to day 4. The parameter was the percentage of parasitemia which was calculated on day 2 to 5. Statistical analysis used was one way Analysis of Variance with a 95% significance level. Parasite growth inhibition percentage data was used to determine the 50% effective dose (ED50) of each drug test dosage by probit regression analysis through SPSS for Windows version 17. The result proves that the fraction of hexane, ethyl acetate and methanol extracts of mangosteen peel has antimalarial activity. Ethyl acetate fraction have better antimalarial activity with the value of ED50 63, 272 mg/KgBW among hexane and methanol fraction (ED50 1930,021 mg/KgBW; 217.616 mg/KgBW).Â Keywords: Antimalarial, Garcinia mangostana, Plasmodium berghei, in vivo